The Encyclopedia of sedimentology - Fairbridge, Rhodes W. (Rhodes Whitmore) 1914-2006.; Bourgeois, Joanne (Stroudsburg, Pa. Dowden, Hutchinson & Ross [New York] Distributed world wide by Academic Press, 1978)
Scholarly work on sedimentology. Each article is signed and has a bibliography. Illustrated. Indexed.
Includes bibliographical references and index.
Keywords: Sedimentology -- Dictionaries; Sedimentologia; Sedimentologie; Rocks, Sedimentary; Sediments (Geology).